2019
DOI: 10.17222/mit.2018.118
|View full text |Cite
|
Sign up to set email alerts
|

Study of the microstructures and mechanical properties of aluminium hybrid composites with SiC and Al2O3

Abstract: Aluminium metal-matrix composites are widely produced with different ceramic compounds as reinforcements to enhance their properties and to suit various structural applications. The present work involves the fabrication of Al7075 composites with silicon carbide (SiC) and aluminum oxide (Al2O3) as reinforcements through stir casting. Four specimens were produced with different compositions comprising SiC (3, 5, 7 and 9 w/%) and Al2O3 2 w/% in all the combinations. Mechanical properties like ultimate tensile str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…The addition of reinforcement materials improves the mechanical integrity of aluminium. Figure 4 was adapted from the study of Pugalenthi et al (2019). It was observed that there was an increase ultimate strength (UTS) from 248 MPa in sample 1 to 325 MPa in Sample 4.…”
Section: Synopsis Of Selected Results and Discussion From Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The addition of reinforcement materials improves the mechanical integrity of aluminium. Figure 4 was adapted from the study of Pugalenthi et al (2019). It was observed that there was an increase ultimate strength (UTS) from 248 MPa in sample 1 to 325 MPa in Sample 4.…”
Section: Synopsis Of Selected Results and Discussion From Literaturementioning
confidence: 99%
“…Mechanical properties of Al7075/SiC/Al 2 O 3 composite (a) yield and ultimate strengths (b) %elongation (c) hardness;1-Al7075 þ 3%SiC þ 2% Al 2 O 3 , 2 -Al7075 þ 5%SiC þ 2%Al 2 O 3 , 3-Al7075 þ 7%SiC þ 2%Al 2 O 3 , 4-Al7075 þ 9%SiC þ 2%Al 2 O 3(Pugalenthi et al, 2019).…”
mentioning
confidence: 99%
“…Debonding leading to ductile fracture seems to be more dominant in samples 2, 3, and 4, which have comparatively low fractions of reinforcements and the presence of aluminium 7075 alloy in the majority. Transgranular fracture was demonstrated in the failure of aluminium 7075 composites, and it is evident that this fracture happens at grain boundaries and becomes disconnected at the moment of failure [51]. In figure 8(c) intergranular fracture can also be seen along with transgranular fracture that occurs along the grain boundaries of the metal.…”
Section: Morphologymentioning
confidence: 90%
“…Additionally, it was noticed that silicon carbide (SiC) is a good strengthener in the alloy of Al [11]. Furthermore, the other employed additives in the previous studies are titanium carbide (TiC) [12], tungsten carbide WC [13], alumina (Al2O3) [14], Si3N4 [15], and AlN [16], as well as the results revealed that the addition of these reinforcements enhanced the performance of aluminum and its alloys. Moreover, the waste utilization in reinforcing the alloys of Al has been verified positive [17].…”
Section: Introductionmentioning
confidence: 94%